New insights toward the transcriptional engineering of proanthocyanidin biosynthesis - Xu, Wenjia (Landes Bioscience, 2014)
Flavonoids are secondary metabolites that play important roles throughout the plant life cycle and have potential human health beneficial properties. Flavonols, anthocyanins and proanthocyanidins (PAs or condensed tannins) are the three main class of flavonoids found in Arabidopsis thaliana. We have previously shown that PA biosynthesis (occurring exclusively in seeds) involves the transcriptional activity of four different ternary protein complexes composed of different R2R3-MYB and bHLH factors together with TRANSPARENT TESTA GLABRA 1 (TTG1), a WD repeat containing protein. We have also identified their direct targets, the late biosynthetic genes. In this study, we have further investigated the transcriptional capacity of the MBW complexes through transactivation assays in moss protoplast and overexpression in Arabidopsis siliques. Results provide new information for biotechnological engineering of PA biosynthesis, as well as new insights into the elucidation of the mechanisms that govern the interactions between MBW complexes and the DNA motifs they can target.